Morphometric and meristic analyses of horse mackerel, Megalaspis cordyla (Linnaeus, 1758) populations along the Indian coast - Sajina, A. M.; Chakraborty, S. K.; Jaiswar, A. K.; Sudheesan, Deepa (Indian Journal of Fisheries, 2013)
Populations of Megalaspis cordyla (horse mackerel) from four areas, two each from the east (Digha and Mandapam regions in the Bay of Bengal) and west (Cochin and Mumbai regions of the Arabian Sea) coasts of the Indian peninsula were studied based on conventional morphometry and meristics. Digital photographs of individual fishes were taken to extract 20 morphometric variables. Nine meristic characters were also counted. The analysis of variance of five morphometric traits showed significant difference between the fish samples of east and west coasts and those traits were eye diameter, prepelvic length, preanal length, anal fin length and caudal peduncle depth. The four traits that revealed location-wise variations were head length, preorbital length, second dorsal fin length and anal fin length. The chi-square test of meristic traits showed significant variation between the Bay of Bengal and Arabian Sea populations and also between the Mandapam and Digha populations. The morphometric and meristic study clearly revealed variations in morphometric traits of fishes from Arabian Sea and Bay of Bengal, which are definitely sufficient to separate these populations.